Survival kinetics of Salmonella Typhimurium in oat and pea protein flours - Ahmad, Nurul Hawa; Jafri, Nur Iman Saliha; Mahmud Ab Rashid, Nor Khaizura; Meor Hussin, Anis Shobirin; Limcharoenchat, Pichamon; Mazón-villegas, Beatriz; Maniam@kumar, Ramhyaa (Universiti Malaysia Sabah, 2024)
Oat and pea protein flours have been used as ingredients for plant-based food products. These low-moisture ingredients have been implicated in Salmonella recalls, most likely due to post-processing contamination. Oat and pea protein flour do not undergo pathogen kill step, especially for minimally cooked or ready-to-eat food. This study aimed to quantify the survival kinetics of Salmonella Typhimurium in oat and pea protein flours at storage temperatures of 4℃ and 25℃. Powders were inoculated at ~8 log CFU/g via seed inoculation method and tested for homogenous Salmonella distribution. The inoculated samples were enumerated on days 0, 3, 5, 7, 21, 35, 49, and 63. This study showed the impact of storage temperatures on S. Typhimurium survival and proved that refrigerated storage did not control microbial growth. The findings suggest that flour treatment should be based on its composition because composition affects Salmonella survival.